Symmetry regimes for circular photocurrents in monolayer MoSe2 - Jorge Quereda (Nature Portfolio, 2018)
Circular photocurrents emerge in atomically thin transition metal dichalcogenides as a result of circular photogalvanic and photon drag effects. Here, the authors identify two different circular photocurrent contributions in monolater MoSe2, dominant at different voltages and with different dependence on illumination wavelength and incidence angles.